Assisted reproductive technology pregnancy complications are significantly associated with endometriosis severity before conception: a retrospective cohort study. Issue 1 (December 2016) - Fujii, Tatsuya; Wada-Hiraike, Osamu; Nagamatsu, Takeshi; Harada, Miyuki; Hirata, Tetsuya; Koga, Kaori; Fujii, Tomoyuki; Osuga, Yutaka
Abstract Background Endometriosis has been shown to be associated with second- to third-trimester pregnancy complications such as preterm birth and placenta previa, but the evidence is inconsistent. We hypothesized that endometriosis severity might affect these inconsistent results. Therefore we aimed to conduct a retrospective cohort study to elucidate whether endometriosis severity is associated with the incidence rates of adverse pregnancy outcomes. Methods The patients who achieved singleton pregnancy by assisted reproductive technology (ART) in our facility between March 2000 and December 2014 (N  = 631) were included in this analysis. Among them, 92 women demonstrated surgically proven endometriosis, and 512 women were shown to not have endometriosis as a complication. Among the 92 cases of endometriosis, 10 were classified as revised American Society for Reproductive Medicine (rASRM) stage I and II, 31 cases were rASRM stage III, and 43 cases were rASRM stage IV; in 8 cases, the rASRM stage was unavailable. Logistic regression analysis was performed to calculate odds ratios (OR) and 95 % confidence interval (CI) for the rates of preterm birth, placenta previa, and small for gestational age. OR were adjusted by age, parity and the number of transferred embryos. Results First we confirmed the frequency of preterm birth and placenta previa were significantly increased in women with endometriosis (preterm birth OR, 2.08; 95 % CI, 1.07–3.89, placenta previa OR, 15.1; 95 % CI, 4.40–61.7), while the frequency of small for gestational age was not. Moreover, we found the frequencies of preterm birth and placenta previa were significantly increased in women with rASRM stage IV endometriosis compared to other two groups: women with rASRM stage I-III endometriosis (preterm birth OR, 7.40; 95 % CI, 1.83–50.3; placenta previa OR, 11.0; 95 % CI, 1.75–216.5) and women without endometriosis (preterm birth adjusted OR, 4.11; 95 % CI, 1.88–8.55; placenta previa adjusted OR, 39.8; 95 % CI, 10.1–189.1). There were no significant difference between women with rASRM I-III endometriosis and women without endometriosis. Conclusions We found that the frequencies of preterm birth and placenta previa were significantly increased in women with endometriosis, and the severity of endometriosis might have an adverse impact on ART pregnancy.